Assessment of early lung disease in young children with CF: A comparison between pressure‐controlled and free‐breathing chest computed tomography. Issue 5 (2nd March 2020) - Oudraad, Merel C. J.; Kuo, Wieying; Rosenow, Tim; Andrinopoulou, Eleni‐Rosalina; Stick, Stephen M.; Tiddens, Harm A. W. M.
Abstract: Background: Chest computed tomography (CT) in children with cystic fibrosis (CF) is sensitive in detecting early airways disease. The pressure‐controlled CT‐protocol combines a total lung capacity scan (TLC PC‐CT) with a near functional residual capacity scan (FRC PC‐CT) under general anesthesia, while another CT‐protocol is acquired during free breathing (FB‐CT) near functional residual capacity. The aim of this study was to evaluate the sensitivity in detecting airways disease of both protocols in two cohorts. Methods: Routine PC‐CTs (Princess Margaret Children's Hospital) and FB‐CTs (Erasmus MC—Sophia Children's Hospital) were retrospectively collected from CF children aged 2 to 6 years. Total airways disease (%disease), bronchiectasis (%Bx), and low attenuation regions (%LAR) were scored on CTs using the Perth‐Rotterdam annotated grid morphometric analysis‐CF method. The Wilcoxon signed‐rank test was used for differences between TLC and FRC PC‐CTs and the Wilcoxon rank‐sum test for differences between FRC PC‐CTs and FB‐CTs. Results: Fifty patients with PC‐CTs (21 male, aged 2.5‐5.5 years) and 42 patients with FB‐CTs (26 male, aged 2.3‐6.8 years) were included. %Disease was higher on TLC PC‐CTs compared with FRC PC‐CTs (median 4.51 vs 2.49; P  < .001). %Disease and %Bx were not significantly different between TLC PC‐CTs and FB‐CTs (median 4.51% vs 3.75%; P  = .143 and 0.52% vs 0.57%; P  = .849). %Disease, %Bx, and %LAR were not significantly different between FRC PC‐CTs and FB‐CTs (median 2.49% vs 3.75%; P  = .055, 0.54% vs 0.57%; P  = .797, and 2.49% vs 1.53%; P  = .448). Conclusions: Our data suggest that FRC PC‐CTs are less sensitive than TLC PC‐CTs and that FB‐CTs have similar sensitivity to PC‐CTs in detecting lung disease. FB‐CTs seem to be a viable alternative for PC‐CTs to track CF lung disease in young patients with CF.